Molecular detection of bee pathogens in honey from various botanical origins - Rossella Tiritelli; Gian Luigi Marcazzan; Cecilia Costa; Antonio Nanetti; Giovanni Cilia (PLoS ONE, 2025)
Honey bees play a crucial role in pollination and global food security, yet their populations are declining due to various environmental stressors, including pathogenic infections. Recently, molecular research in honey has been proposed as a powerful, non-invasive tool for detecting and monitoring honey bee pathogens and parasites. This study analysed 679 honey samples from all Italian regions to detect the presence of 8 pathogens (DWV, CBPV, ABPV, BQCV, KBV, Nosema ceranae , Crithidia mellificae , Lotmaria passim ) using qPCR assays. Overall, 97.5% of the honey samples tested positive for at least one pathogen, with the most prevalent being DWV (81.7%), N. ceranae (56.1%), and CBPV (56.0%). None of the samples tested positive for KBV or C. mellificae . Statistical analyses revealed significant variations in pathogen prevalence and copy number depending on the honey type, geographic origin and correlations among different pathogens. Additionally, co-presence was common, with over 77% of honey samples containing multiple pathogens. These findings support honey analysis as an effective and valid method for pathogen surveillance in honey bee populations. By providing valuable insights into disease dynamics, this approach could enhance epidemiological monitoring and contribute to improved honey bee health management strategies.